Synthesis, Characterization and Visible-Light Photocatalytic Activity of Solid and TiO2-Supported Uranium Oxycompounds - Mikhail Lyulyukin; Tikhon Filippov; Svetlana Cherepanova; Maria Solovyeva; Igor Prosvirin; Andrey Bukhtiyarov; Denis Kozlov; Dmitry Selishchev (Nanomaterials, 2021)
In this study, various solid uranium oxycompounds and TiO2-supported materials based on nanocrystalline anatase TiO2 are synthesized using uranyl nitrate hexahydrate as a precursor. All uranium-contained samples are characterized using N2 adsorption, XRD, UV–vis, Raman, TEM, XPS and tested in the oxidation of a volatile organic compound under visible light of the blue region to find correlations between their physicochemical characteristics and photocatalytic activity. Both uranium oxycompounds and TiO2-supported materials are photocatalytically active and are able to completely oxidize gaseous organic compounds under visible light. If compared to the commercial visible-light TiO2 KRONOS® vlp 7000 photocatalyst used as a benchmark, solid uranium oxycompounds exhibit lower or comparable photocatalytic activity under blue light. At the same time, uranium compounds contained uranyl ion with a uranium charge state of 6+, exhibiting much higher activity than other compounds with a lower charge state of uranium. Immobilization of uranyl ions on the surface of nanocrystalline anatase TiO2 allows for substantial increase in visible-light activity. The photonic efficiency of reaction over uranyl-grafted TiO2, 12.2%, is 17 times higher than the efficiency for commercial vlp 7000 photocatalyst. Uranyl-grafted TiO2 has the potential as a visible-light photocatalyst for special areas of application where there is no strict control for use of uranium compounds (e.g., in spaceships or submarines).